Die Möglichkeiten und Grenzen der Messbarkeit von Musikgeschmack - Fleischer, Benedikt; Justus Liebig University Giessen (My University, 2012)
The present article examines the study series »The Do Re Mis of Everyday Life: The Structure and Personality Correlates of Music Preferences,« carried out by Rentfrow and Gosling in 2003, and focuses on the creation of the »Short Test of Music Preferences« and the registration of the preference dimensions in the second study. Thus, in interdisciplinary research, the previous research of music taste, genre and test theory are used as the standard of comparison. Numerous test-theoretical deficiencies, missing compliances of psychological quality criteria and insufficient definitions of concept are revealed. Genre terms prove to be too abstract and thus cannot capture the complexity of underlying social and cultural systems. Ambiguous and inappropriate terms are used for the interpretation of the factors without considering music experts or music taste research. Subsequently, it is recommended to equate music preferences with the established attitude construct. In addition, stable, canonised genre codes should be used as preference guidelines.
Keywords: ddc:780